The Experience of Mothers Caring for Children with Disabilities at the Persatuan Rakyat Indonesia Special School in Pekalongan, Central Java: A Phenomenological Study - Maulinda, Amanda Via; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2022)
Background: Disabilities are often called physical, mental and sensory disabilities or disorders that limit a person’s ability to carry out daily activities. Parenting a child with a disability is not easy because the child cannot perform any activities independently and the child’s behavior is not controlled. This results in a negative impact on the mother psychologically, physically and can disrupt family dynamics such as domestic violence and quarrels. This study aimed to explore the experiences of mothers caring for children with disabilities. Subjects and Method: This was a qualitative study with a phenomenological approach, conducted at the Persatuan Rakyat Indonesia Special School (SLB) in Pekalongan, Central Java. The study subjects were selected purposively as many as four participants, namely housewives without caregivers who have children with physical disabilities, deaf-speech, and mentally retarded children. Data were collected using in-depth interview technique. The tools used in this research are camera, recording device and interview guide. Data analysis using Colaizz’s method. Results: This qualitative research resulted in seventeen themes that show the experience of mothers in caring for children with disabilities, namely destiny, mother’s burden, mother’s initial psychological response, emotional changes, behavioral changes, limited funds, obstacles in daily life, social stigma, financial support, social support, assistance efforts. health workers, efforts to seek other assistance, the attitude of the mother when the child conveys a choice, the attitude of the mother when the child acts inappropriately, the expectations and limitations of special health services for disability, the wisdom of spiritual improvement and bathing. Conclusion: Mother’s experience in caring for children with disabilities found unstable emotional changes, excessive worry and excessive attention. Support is very influential for mothers in the form of information support, extended family support, nuclear family and the surrounding community. During caring for children with disabilities, mothers gain wisdom, namely increasing patience and gratitude.